Review Review: Review of the Relationship Between Pesticide Exposure and Risk of Renal Failure Disease - Silitonga, Jessica Christin (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
Pesticides can have serious adverse effects on health, especially kidney failure, even though they are intended to manage pests. Examined in this scientific review is the connection between farmers' compromised kidney function and pesticide exposure. A laboratory method that involved taking samples of blood and urine and using High-Performance Liquid Chromatography (HPLC) to analyze pesticide levels revealed a positive relationship between exposure to pesticides, particularly organophosphates, and higher levels of creatinine and urea, which are markers of kidney damage. Twenty-four percent of Indonesian farmers suffer from chronic kidney disease (CKD), according to data from five out of twelve publications. Poor personal hygiene and insufficient use of personal protective equipment (PPE) are risk factors that contribute to kidney damage. Pesticides may induce oxidative stress and inflammation in kidney tissues, according to a discussion of pathophysiological mechanisms. To safeguard farmers' kidney health, this journal review highlights the significance of routine health monitoring and instruction on safe pesticide use. To comprehend the underlying mechanisms of kidney damage caused by pesticide exposure and to create efficient preventative measures, more research is required.